National and Regional Coordinates of the Real Convergence Process Intensity in the Enlarged European Union - Iulia Andreea Bucur (CES Working Papers, 2012)
Real convergence of EU economies can be approached from the perspective of close relations between the state of homogeneity and the existence of conditions that can facilitate it. In this paper we test the hypothesis of beta convergence at national level for the group formed by all 27 EU member states (EU-27), for one of the old Member States (founding members and countries that joined in the first three waves of EU enlargement) (EU-15) and one of the new Member States (EU-10+2) (countries that joined in the last two waves of EU enlargement) and also at regional level for all 271 NUTS 2 regions. For reasons of comparison we will use the same indicator GDP per capita at purchasing power standards (PPS) for analysis of both levels. Given the availability of statistical information, we quantified applying the regression model, the marginal effect from GDP per capita growth caused by the change of condition expressed by the initial development stage.
Keywords: C20; F15; O16; 330; EU member states; NUTS 2 regions; beta convergence; GDP per capita growth rate; regression model Romania